Can Currently Suggested Quality Indicators Be Transferred to Meningioma Surgery?—A Single-Center Pilot Study - Spille, Dorothee C.; Lohmann, Sebastian; Schwake, Michael; Spille, Johannes; Alsofy, Samer Zawy; Stummer, Walter; Brokinkel, Benjamin; Schipmann, Stephanie (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background Risk stratification based on standardized quality measures has become crucial in neurosurgery. Contemporary quality indicators have often been developed for a wide range of neurosurgical procedures collectively. The accuracy of tumor-inherent characteristics of patients diagnosed with meningioma remains questionable. The objective of this study was the analysis of currently applied quality indicators in meningioma surgery and the identification of potential new measures.Methods Data of 133 patients who were operated on due to intracranial meningiomas were subjected to a retrospective analysis. The primary outcomes of interest were classical quality indicators such as the 30-day readmission, 30-day reoperation, 30-day mortality, 30-day nosocomial infection, and the 30-day surgical site infection rate. Uni- and multivariate analyses were performed. The occurrence of a new postoperative neurologic deficit was analyzed as a potential new quality indicator.Results The overall unplanned readmission rate was 3.8%; 13 patients were reoperated within 30 days (9.8%). The 30-day nosocomial infection and surgical site infection rates were 6.8 and 1.5%, respectively. A postoperative new neurologic deficit or neurologic deterioration as a currently assessed quality feature was observed in 12 patients (9.2%). The edema volume on preoperative scans proved to have a significant impact on the occurrence of a new postoperative neurologic deficit (p = 0.023).Conclusions Classical quality indicators in neurosurgery have proved to correlate with considerable deterioration of the patient's health in meningioma surgery and thus should be taken into consideration for application in meningioma patients. The occurrence of a new postoperative neurologic deficit is common and procedure specific. Thus, this should be elucidated for application as a complementary quality indicator in meningioma surgery.
Keywords: meningioma; microsurgery; new neurologic deficit; outcome; quality indicators